(untitled) (Entrepreneurship Journal for Finance and Business, 2020)
Intangible assets are important for many establishments in most sectors, such as the industrial ones, and the need to measure them to reduce the volume of risks, so the research dealt with the issue of measuring intangible assets and their impact on investment decisions in shares, where the problem of research is embodied in the intangible and intangible existence of intangible assets, which makes The process of measuring it accounting "is a difficult and complex process and includes many financial risks related to the uncertainty in this regard, which gives a" large "aspect of the difficulty in linking it with investor decisions and determining its impact on these decisions. Therefore, the research aims to determine the extent of the impact of measuring Intangible assets in investment decisions in companies through their influence on the market values ​​of their shares,The research is based on testing the following hypothesis: “The measurement of intangible assets affects investment decisions by causing fluctuations in the market value of companies’ shares. ”A number of conclusions were drawn up, the most important of which are: The relationship between the ratios and amounts of intangible assets on the one hand and the market values ​​of companies’ shares on the one hand was taken. Other, the shape and manner of fluctuation, as they are direct and opposite, and from year to year, and the reason for this fluctuation is that the values ​​and ratios of intangible assets are only one of a number of factors that affect the behavior and decisions of investors in companies’ shares through their influence on the decisions of buying and selling their shares. It affects its values ​​in the financial market indirectly, and the research came up with a number of recommendations, the most important of which are: studying and monitoring the behavior of investors, especially their decisions related to buying and selling companies’ shares, and working to reduce the negative impact of financial information related to intangible assets on these decisions and behaviors and its reflection on the market values ​​of shares .